Insights on effector candidates of Austropuccinia psidii: identification, characterization and comparative genomic analysis - Hayashibara, Carolina Alessandra de Almeida (2021)
Myrtle rust is a disease caused by the biotrophic fungus Austropuccinia psidii. Biotrophic fungi require living tissues to obtain nutrients and to develop, establishing a close relationship with the host. Since the first contact between pathogen and host, several molecules of both are involved. Information on the interaction between A. psidii and the host is scarce, due to a large number of infected Myrtaceae species, in addition to the biotrophic lifestyle of A. psidii, which limits the in vitro manipulation. To overcome the defense mechanisms of plants, fungi can release effectors during the infection. In general, effectors are molecules secreted by the pathogen that may alter the host\'s physiology for successful infection and colonization. Thus, the characterization of secreted effectors is a crucial strategy to understand the mechanisms involved in the host infection by the pathogen. Chapter 1 shows the first study on effector candidates of A. psidii biotype MF-1. First, 255 effector candidates were identified, and in silico prediction of localization and functions was performed, the most effector candidates were predicted as apoplastic and as hypothetical proteins with unknown functions. By RT-qPCR, we performed in vitro expression validation of seven randomly selected effector candidates, using as stimulus cuticular waxes extracted from leaves of resistant and susceptible Eucalyptus species to the pathogen, E. urophylla and E. grandis, respectively. The seven effector candidate\'s expression was modulated according to cuticular waxes. Two effector candidates, Ap28303 and Ap30385, were cloned into binary vectors containing the G3GFP (Green Fluorescent Protein) protein, and agroinfiltrated in leaves of Nicotiana benthamiana. Agroinfiltration was performed to observe the subcellular localization of the effector candidates, however the effector candidate Ap30385 was not observed in any compartment, and the effector candidate Ap28303 was observed accumulating in the nucleus. For the first time, A. psidii effector candidates were identified, as well as the subcellular localization of one effector candidate. In Chapter 2, the identification and comparison of effectors from three A. psidii biotypes, a pandemic biotype from Australia, a biotype from South Africa, and the MF-1 biotype from Brazil were carried out. It was observed a greater number of effectors from pandemic biotype compared with the others, however, it was not found differences in the predicted localization of effector candidates. By homology analysis, it was observed that the Australian biotype was more distant from the other two, regarding the effector candidates, showing the highest number of exclusive proteins. From PCR validation, the most effector candidates showed conserved among the tested biotypes, and polymorphisms were found. Therefore, deep studies are required for a better understanding of variation importance on host range. Certainly, this pioneering study will enable new studies about effector candidates from A. psidii, improving the comprehension of effector evolution and host relationship, as well offering a profile to further detailed characterization of other effector candidates.